ESG Investing from the Perspective of 4Ps of Marketing - Nadeem, Farrukh; Singh, Ajay (Prabandhan: Indian Journal of Management, 2024)
Purpose : This research paper aimed to investigate the global and Indian context of environmental, social, and governance (ESG) implementation and to assess the feasibility of positioning â€œESGâ€ as a product through government and financial institutions. India had unique obstacles to overcome, as well as a large backlog of unmet goals in relation to its social and environmental obligations. The possibility of achieving net zero emissions through implementing ESG norms existed, provided they were effectively promoted. The paper explored utilizing promotion methods by governmental entities to enhance ESG adoption and awareness. Design/Methodology/Approach : The study was an exploratory examination of research carried out by various investment companies, consulting firms, international research organizations, research bloggers, and ESG rating agencies. Additionally, it included presentations made by speakers at conferences and award ceremonies that emphasized the application of ESG. Findings : This perspective paper underscored the significance of ESG investing and framed the concept through the lens of the 4Ps of marketing. Practical Implications : A number of factors, including population growth, high inflation, corruption, economic uncertainty, and the demand for natural resources, have always made it difficult for the nation to achieve its social and environmental goals. The goal of reaching â€œnet zeroâ€ by 2070 posed a substantial execution and achievement hurdle. This study showed how national ESG product promotion may have increased public knowledge of the advantages of ESG implementation. Originality/Value : This paper has tried to relate ESG investing to the concept of marketing, drawing parallels with social initiatives marketed by the government.